Promising direction of jurisprudence: the transformation of the legal system in the context of globalization - Калюжний, Ростислав Андрійович; Сопілко, Ірина Миколаївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2011)
Scientific review of the monograph of L.G. Udovyk "Transformation of the legal system in the context of globalization: anthropological dimension."